Biotechnology for Fuels and Chemicals 2003
DOI: 10.1007/978-1-4612-0057-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Ammonia-Treated Rice Straw

Abstract: Rice straw pretreated with liquid anhydrous ammonia was hydrolyzed with cellulase, cellobiase, and hemicellulase. Ammonia-processing conditions were 1.5 g of NH3/ g of dry matter, 85°C, and several sample moisture contents. There were four ammonia addition time (min)-processing time (min) combinations. Sugars produced were analyzed as reducing sugars (dinitrosalicylic acid method) and by high-performance liquid chromatography. Monomeric sugars increased from 11 % in the nontreated rice straw to 61% of theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…The water composition of the fruits ranged from 94.33 ± 0.58% to 96.37 ± 0.46%. These results differ from those of Pinela et al [22] this difference is due to the different substrates used. Indeed, these authors showed tomato water contents ranging from 90.63 to 93.70%.…”
Section: Discussioncontrasting
confidence: 99%
“…The water composition of the fruits ranged from 94.33 ± 0.58% to 96.37 ± 0.46%. These results differ from those of Pinela et al [22] this difference is due to the different substrates used. Indeed, these authors showed tomato water contents ranging from 90.63 to 93.70%.…”
Section: Discussioncontrasting
confidence: 99%
“…5 Previous work has shown this process to give near theoretical yields of glucose on many different types of biomass. [6][7][8][9] AFEX also compares favorably with other pretreatment methods, producing high The goal of this study, then, is to determine the optimal conditions in terms of temperature and ammonia loading for the AFEX process on DDGS to provide maximum glucose yields. The effect of adding xylanase and amylase to hydrolyze xylose and starch, respectively, was also determined.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose content was obtained using cold anthrone reagent (9). Hemicellulose was calculated by using a standard fiber analysis procedure (10,11). Lignin content and ash content was determined using TAPPI (Technical Association of Pulp and Paper Institute, Atlanta, Georgia, USA, 1992) standard methods (12).…”
Section: Compositional Analysismentioning
confidence: 99%